Antimicrobial Activity of Nanochitosan Shrimp Shell as a Hands Sanitizer - Safrina Dyah Hardiningtyas; Dona Fradilla Bahri; Pipih Suptijah (Journal of Marine and Coastal Science, 2022)
Chitosan is a biopolymer that can be extracted from crustaceans, such as shrimp shells. Chitosan is widely used in various fields, such as pharmaceuticals, food, and cosmetics because it is biodegradable, non-toxic, and has antibacterial activity. Nanochitosan is a dosage form based on nanotechnology which has more reactive properties. The purpose of this study was to characterize chitosan and nanochitosan and evaluate the effectiveness of nanochitosan as an antibacterial in hand sanitizer. The tests carried out included analysis of the functional group of chitosan with FTIR, particle size analysis with particle size analyzer, morphological analysis of nanochitosan with SEM, and analysis of the effectiveness of hand sanitizers. The test chitosan used had a degree of deacetylation of 85.94%. The particle size distribution of nanochitosan was 140.94 nm with a polydispersion intensity (PDI) of 0.5830. The results of the antibacterial effectiveness test of nanochitosan as a hand sanitizer showed that the higher the concentration of nanochitosan used, the total bacterial colonies would decrease. The concentration of 2000 ppm nanochitosan can reduce 93.4% of bacterial colonies on probandus hands, and this activity is known to be not significantly different from commercial hand sanitizers.